Validating Left Ventricular Filling Pressure Measurements in Patients with Congestive Heart Failure: CardioMEMS™ Pulmonary Arterial Diastolic Pressure versus Left Atrial Pressure Measurement by Transthoracic Echocardiography - Sunit Tolia; Zubair Khan; Gunjan Gholkar; Marcel Zughaib (Cardiology Research and Practice)
Background. Routine ambulatory echocardiographic estimates of left ventricular (LV) filling pressures are not cost-effective and are occasionally fraught with anatomic, physiologic as well as logistical limitations. The use of implantable hemodynamic devices such as CardioMEMS Heart Failure (HF) System has been shown to reduce HF-related readmission rates by remote monitoring of LV filling pressures. Little is known about the correlation between CardioMEMS and echocardiography-derived estimates of central hemodynamics. Methods. We performed a prospective, single-center study enrolling seventeen participants with New York Heart Association functional class II-III HF and preimplanted CardioMEMS sensor. Simultaneous CardioMEMS readings and a limited echocardiogram were performed at individual clinic visits. Estimated left atrial pressure (LAP) by echocardiogram was calculated by the Nagueh formula. Linear regression was used as a measure of agreement. Variability between methods was evaluated by Bland–Altman analysis. Results. Mean age was 74 ± 9 years; 59% (10/17) were males. LV systolic dysfunction was present in 76% (13/17) of subjects. Mean PAdP was 18 ± 4 mmHg and 19 ± 5 mmHg for CardioMEMS and echocardiographic-derived estimates, respectively, with a significant correlation between both methods (r2=0.798,  p≤0.001). Conclusions. Our study illustrates a direct linear correlation between PAdP measured by CardioMEMS and simultaneous measurement of LV filling pressures derived by echocardiography.